Rozwój szkolnictwa wyższego w Polsce - w trzech odsłonach myśli strategicznej = Polish universities in three views of strategic thought - Dziedziczak-Foltyn, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The starting point in the reflections on strategic thought will be the question of how much the present state of higher education in Poland results from the conscious policy of Polish authorities. Spontaneous marketization of higher education in Poland within the last 20 years appeared to show the absence of education state policy, however, topdown state regulations changing the rules of market game could be observed. And today, despite higher education reform actions initiated by the government in 2008, there are the voices about the absence of education state policy and substantive public debate on it.
Keywords: szkolnictwo wyższe; rozwój; Polska